2015
DOI: 10.1007/s10517-015-2814-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interleukin-4 on Peripheral Blood Leukocytes in Rats with Various Behavioral Characteristics During Acute Stress

Abstract: We studied the effect of anti-inflammatory cytokine IL-4 (5 μg/kg intraperitoneally) on peripheral blood leukocytes in Wistar rats with various behavioral characteristics during acute emotional stress (1-h immobilization with simultaneous subthreshold electrocutaneous stimulation). IL-4 reduced the differences in blood leukocyte count in rats with various behavioral characteristics, which was related to a significant decrease in this parameter in active animals. IL-4 injection to active animals was accompanied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Stress is a major cause of functional and structural disorders in various organs, including the male reproductive organs, which can lead to sub-fertility or infertility (Popović and Pajović, 2010;Reis et al, 2011;Bitgul et al, 2013;Everds et al, 2013;Naninck et al, 2015). Numerous studies in animals and humans have shown that stress, in addition to significantly increasing corticosterone levels, has adverse effects on the cardiovascular, digestive, immune, and reproductive systems (İzgüt-Uysal et al, 2014;Matsuura et al, 2015;Pertsov et al, 2015;Prabsattroo et al, 2015). In males, stress decreases the levels of gonadotropin-releasing hormone (GnRH), folliclestimulating hormone (FSH), and luteinizing hormone (LH), which leads to reductions in testosterone levels (Retana-Márquez et al, 2003;Rai et al, 2004;Lin et al, 2014;Prabsattroo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Stress is a major cause of functional and structural disorders in various organs, including the male reproductive organs, which can lead to sub-fertility or infertility (Popović and Pajović, 2010;Reis et al, 2011;Bitgul et al, 2013;Everds et al, 2013;Naninck et al, 2015). Numerous studies in animals and humans have shown that stress, in addition to significantly increasing corticosterone levels, has adverse effects on the cardiovascular, digestive, immune, and reproductive systems (İzgüt-Uysal et al, 2014;Matsuura et al, 2015;Pertsov et al, 2015;Prabsattroo et al, 2015). In males, stress decreases the levels of gonadotropin-releasing hormone (GnRH), folliclestimulating hormone (FSH), and luteinizing hormone (LH), which leads to reductions in testosterone levels (Retana-Márquez et al, 2003;Rai et al, 2004;Lin et al, 2014;Prabsattroo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, increased expression of such cytokines due to a history of uncontrollable stress during pregnancy might be associated with higher odds of occurrence of lung inflammation in the offspring. It is worth noting that recent studies indicate that IL‐4 has a protective and anti‐inflammatory role (Kalinichenko, Pertsov, & Koplik, ; Pertsov, Koplik, & Kalinichenko, ). Therefore, one might infer that the apparent discrepancy between the results corresponding to IL‐4 and the other investigated cytokines is in fact a highly consistent phenomenon.…”
Section: Discussionmentioning
confidence: 98%